ANALYSIS OF JUDGES' FORGIVENESS (RECHTERLIJK PARDON) FOR CHILDREN PERPETRATED BY THEFT UNDER AGGRAVATING CIRCUMSTANCES (CASE STUDY OF DECISION NO. 2/PID.SUS-ANAK/2021/PN RGT) - Atika Ramadhani Tarigan; Ferdy Saputra; Laila M. Rasyid (CV. RADJA PUBLIKA, 2025)
The concept of Rechterlijk Pardon gave judges the authority to exclude the implication of punishment, especially in legal violations involving children. This research aims to analyze the application of the concept in a case involving a child committing theft, referring to Decision Number 2/Pid.Sus-Anak/2021/PN Regt. The case showed the judge's policy of choosing not to impose a sentence even though the child was declared guilty. The focus of the study was on how the judge's pardon was implemented in the juvenile criminal justice system in Indonesia, as well as the alignment of the decision with the principle of Rechterlijk Pardo. The method used was normative juridical with case study approach, collecting information sourced from statutory provisions and court decisions. The findings shwed that the judge chose not to impose a sentence on the child who committed theft even though the elements of the offense were proven. The judge's considerations included the child's age, family background, educational history, remorse, and potential for social rehabilitation. The judge argued that punishment would not bring about substantive justice and might harm the child's future life. The essence of Rechterlijk Pardon is a reflection of the transition toward a justice system that prioritizes recovery and restorative justice. Judges have a central role in ensuring harmony between law enforcement and safeguarding children's rights. Thus, this concept becomes an important instrument for giving a second chance to children in conflict with the law.